Posted by **Carly** on Tuesday, July 28, 2009 at 12:05am.

If f(x)=x^2-2 and g(x)=1/(3x) (x does not equal 0), find (fxg)(-2)

## Answer this Question

## Related Questions

- Math - If f(x)=x^2-2 and g(x)=1/(3x) (x does not equal 0), find (f+g)(x) and f(...
- math - Determine whether each of the following statements is true or false. ...
- algebra - find (FxG)(X) and (GxF)(X) when f(x)=5x^2-1 and g(x)=2/x
- college - find (FxG)(X) and (GxF)(X) when f(x)=5x^2-1 and g(x)=2/x
- math - if f(x)= 5x+7 and g(x)=x^2-2 write the functions a. (fxg)(x) b. f(g(x))
- math - sketch the feasible region for this system of the inqualities and find ...
- Advanced Math - A circle of center (-3 , -2) passes through the points (0 , -6) ...
- Math - I have two problemson polygonal convex sets which I do not understand. ...
- Math - 1) When will the dependent variable in the equation y=√x+4-3 equal...
- math - The function f(x)is defined as f(x)={-2x+3: if -2 less than or equal to &...